Correction: Synthesis of highly substituted 2-spiropiperidines. Issue 36 (10th August 2018) - Griggs, Samuel D.; Thompson, Nathan; Tape, Daniel T.; Fabre, Marie; Clarke, Paul A.
Abstract : Correction for 'Synthesis of highly substituted 2-spiropiperidines' by Samuel D. Griggs et al., Org. Biomol. Chem., 2018, DOI: 10.1039/c8ob01272e.